Examining the Use and Construct Fidelity of Technology-Enhanced Items Employed by K-12 Testing Programs. Issue 4 (2nd October 2019) - Russell, Michael; Moncaleano, Sebastian
ABSTRACT: Over the past decade, large-scale testing programs have employed technology-enhanced items (TEI) to improve the fidelity with which an item measures a targeted construct. This paper presents findings from a review of released TEIs employed by large-scale testing programs worldwide. Analyses examine the prevalence with which different types of TEIs are employed and the content areas and grade levels in which they are employed. The analyses apply the Technology-Enhanced Item Utility Framework to examine the fidelity with which current TEIs represent targeted constructs. The analyses indicate that the most common type of TEI employed by testing programs is a drag-and-drop response interaction. Analyses indicate that approximately 40% of the TEIs examined provide a high-level of construct fidelity, while an approximately equal proportion provide low construct fidelity. Finally, the data indicate that a large portion of drag-and-drop items are of low fidelity while other TEI types provide moderate or high fidelity.